Tandem-L Instrument Design and SAR Performance Overview - Younis, M.; Huber, S.; Herrero, C. Tienda; Krieger, Gerhard; Moreira, Alberto; Uematsu, A.; Sudo, Y.; Nakamura, R.; Chishiki, Y.; Shimada, M. (IEEE International Geoscience and Remote Sensing Symposium (IGARSS), 2014)
Tandem-L is a proposal for an innovative interferometric radar mission to monitor the Earth system and its intricate dynamics. Important mission objectives are global inventories of forest height and above-ground biomass, largescale measurements of Earth surface deformations due to plate tectonics, erosion and anthropogenic activities, observations of glacier movements and 3-D structure changes in land and sea ice, and the monitoring of ocean surface currents. A detailed description of the mission goals can be found in [1]. The mission concept is based on co-flying two fully-polarimetric L-band SAR satellites in a close formation. Tandem-L employs new techniques and advanced technologies to achieve its ambitious mission goals. The feasibility of a joint DLR/JAXA mission is currently being investigated in the scope of a pre-phase A study. This paper provides an overview of the Tandem-L instrument design concept and its performance predictions. Innovative aspects like the employment of advanced digital beamforming techniques and operation in a variety of imaging modes are detailed.
DLR Import::2019-04-03